LONELINESS IN KATHERINE MANSFIELD’S SHORT STORIES (Scientific journal of the Fergana State University, 2023)
This article aims to dis cuss the theme of loneliness of women in Katherine Mansfield’s short stories. Her short stories show women’s role, status and values in the society. Mansfield wrote many stories about lonely single women who lead poor hard lives and who are emotionally or physically deprived. Mansfield feels  character’s inner world and their life.